Exploring jamun diversity: few unique selections (Current Horticulture, 2024)
Jamun [Syzygium cuminii (L.) Skeels] is an evergreen tree of tropical and subtropical region. Sizable diversity of jamun is observed in Maharashtra, Rajasthan, Gujarat, Uttar Pradesh, Haryana, West Bengal, and the Western Ghats region (Daware et al., 1985; Malik et al., 2017, Tripathi et al., 2018). Being a cross-pollinated crop, and propagated from time immemorial by seeds, considerable variability in fruit size, shape and biochemical constituents exists in it's collections. Selection is the only improvement method widely adopted and several varieties are being released (Keskar et al., 1989). Big fruit size with small seeds and higher pulp recovery is the major trait preferred by consumers. Extensive surveys were undertaken in different parts of the country lead to several collections of jamun with superior quality and higher pulp recovery. These collections were planted at ICAR-Indian Institute of Horticulture Research, Bengaluru and in- situ and ex situ evaluation of these collections is in progress. A few unique genotypes were identified.